Promoting gender equality in Spanish Science - Delgado, Leticia (Investigaciones Feministas (Feminist Research), 2015)
Gender equality in science is an area of public intervention of recent creation in Spain. In this article I explore its process of formation (2002-2014) attending to the foreseeable impact of two kinds of phenomena: on the one hand, a solid pool of European proposals; on the other, two turnovers in national government in 2004, from PP to PSOE, and in 2011/2012, from PSOE to PP. Firstly I characterize its entry in the national governmental agenda following a mixed approach –policy window plus policy transfer—, and the creation and development of the Women and Science Unit as the central axe of the governmental intervention in this policy sector. From interviews to people involved in formulation and implementation of such measures en 2006/2010 I (re)construct the problem representation of gender inequity in public universities and research institutes. After having identified the major changes observed in this policy since the last government turnover, I offer some conclusions about the relative influence of international and domestic factors in the process of formation of the Spanish gender equality policy in science.